Are hypermassive neutron stars stable against a prompt collapse?. Issue Volume 16:Issue S363(2020) (June 2020) - Szewczyk, Paweł; Gondek-Rosińska, Dorota; Kolasa, Kamil; Mehta, Parita
Abstract: Differential rotation in neutron stars allows for significantly larger masses than rigid rotation. Some of those hypermassive objects are, however, unstable and collapse to a black hole immediately after formation. Yet, the exact threshold of dynamical stability is still unknown. In our work we explore the limits on masses of neutron stars with various degrees of differential rotation which could be stable against a prompt collapse to a black hole by using turning-point (j-constant) criterion. We considered both spheroidal and quasi-toroidal differentially rotating neutron stars described by the polytropic equation of state. We find that massive configurations could be temporarily stabilized by differential rotation. Such objects are important sources of gravitational waves. Our results are a starting point for more detailed studies of stability using hydrodynamical codes.